Selective transitional zone sampling approach versus random biopsy in cases with malignant liver masses: Is there any superiority? - Kosti Can ÇALIŞKAN; Banu ÖZGÜVEN; Mehmet Sait BUĞDACI; Emin ÇAKMAKCI; Umut Perçem ORHAN; Mehmet ERTÜRK; Zeki KARPAT; Muzaffer BAŞAK; Fatih SELÇUKBİRİCİK (Turkish Journal of Gastroenterology, 2019)
-